Reversal of secondary pulmonary hypertension by axial and pulsatile mechanical circulatory support - Torre-Amione, Guillermo; Southard, Robert E.; Loebe, Matthias M.; Youker, Keith A.; Bruckner, Brian; Estep, Jerry D.; Tierney, Megan; Noon, George P. (The Journal of heart and lung transplantation, 2010)
Pulmonary hypertension associated with chronic congestive heart failure posses a significant risk of morbidity and death after heart transplantation. Isolated observations suggest that chronic ventricular unloading may lead to normalization of pulmonary pressures and thus render a patient likely to be a heart transplant candidate. This study is a retrospective analysis of 9 heart failure patients with secondary pulmonary hypertension (transpulmonary gradient [TPG] > 15 mm/Hg). Two were treated with a pulsatile left ventricular assist device (LVAD) and 7 with an axial-flow LVAD. After LVAD support, mean pulmonary artery pressure decreased from 39 ± 7 to 31 ± 5 mm Hg, and the TPG decreased from 19 ± 3 to 13 ± 4 mm Hg ( p < 0.01). The 1-year Kaplan–Meier survival curve for patients with pre-LVAD TPG > 15 mm Hg vs those with TPG < 15 mm Hg showed no difference in survival ( p = 0.6). This finding was supported by analysis of a large multi-institutional cohort obtained from the Organ Procurement and Transplantation Network database, where no differences in survival were found in the same groups. Pulmonary hypertension that is secondary to congestive heart failure, as defined by a TPG > 15 mm Hg can be reversed by the use of pulsatile and axial-flow LVADs; furthermore, post-transplant survival for patients with secondary pulmonary hypertension treated with an LVAD was no different than for those without pulmonary hypertension who received LVAD support.